Claude Ake, A political Economy of Africa/ London: Longman, 1981/ 196 s., 87/OO kr Jerker Carlsson, Limits to Structural Change, Uppsala: Scandinavian Institute of African Studies, 1981, 285 s., 120,00 Skr. - Jensen, Leif; Christiansen, Peter Munk (Politica, 1982)
-